2021
DOI: 10.32598/ahs.10.4.281.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Staff: Perceived Benefits, Barriers, and Self-efficacy

Abstract: Background & Aims of the Study: A major factor affecting health is regular physical activity. Physical activity reduces the risk of infectious diseases. The current study aimed to investigate the Perceived benefits, barriers, and self-efficacy of physical activity of the administrative staff of Shahid Beheshti University of Medical Sciences in 2018. Materials and Methods: In this descriptive-analytical study, a sample of 300 employees of the administrative staff of Shahid Beheshti University of Medical Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of the literature review showed that factors such as knowledge (4,14,15), PA literacy (16), motivation to follow (14,17), behavioral consequences (14,18), positive attitude towards PA (14)(15)(16)18), behavioral skills (19), perceived sensitivity and intensity (14,15,18), perceived benefits (14,20,21,22), self-efficacy (14,15,18,20,22), social support (4,14,15,18,23), social norms (15,17), structural factors and enabling factors (14,24,25), policies and laws (14,21) environmental factors (the provision of facilities and resources) (15,16,19,24) and organizational support (20,25,26) are effective factors of PA in the workplace.…”
Section: Step 1: Needs Assessmentmentioning
confidence: 99%
“…The results of the literature review showed that factors such as knowledge (4,14,15), PA literacy (16), motivation to follow (14,17), behavioral consequences (14,18), positive attitude towards PA (14)(15)(16)18), behavioral skills (19), perceived sensitivity and intensity (14,15,18), perceived benefits (14,20,21,22), self-efficacy (14,15,18,20,22), social support (4,14,15,18,23), social norms (15,17), structural factors and enabling factors (14,24,25), policies and laws (14,21) environmental factors (the provision of facilities and resources) (15,16,19,24) and organizational support (20,25,26) are effective factors of PA in the workplace.…”
Section: Step 1: Needs Assessmentmentioning
confidence: 99%